Development of elements of the quality management system of the reception and accommodation service in the hotel - Kuzmin, Oleg; Chernenko, Dmytro; Symonova, Oleksandra; Velichko, Vladimir (My University, 2018)
This article describes reception and accommodation service as an integral part of the hotel industry, which aims to meet the needs of hotel guests. The basic level of quality control of the reception and accommodation service and basic teaching methods in this service.
Keywords: кафедра технології ресторанної і аюрведичної продукції; quality; control system by quality; hotel industry; service of reception and accommodation; якість; система управління якістю; готельне господарство; служба прийому і розміщення качество; система управления качеством; гостиничное хозяйство; служба приема и размещения